Curcumin delivered through bovine serum albumin/polysaccharides multilayered microcapsules. (January 2016) - Paşcalău, V; Soritau, O; Popa, F; Pavel, C; Coman, V; Perhaita, I; Borodi, G; Dirzu, N; Tabaran, F; Popa, C
The aim of the paper is to obtain and characterize k-carrageenan–chitosan dual hydrogel multilayers shell BSA gel microcapsules, as a carrier for curcumin, and as a possible antitumoral agent in biological studies. We used the CaCO3 template to synthesize non-toxic CaCO3 /BSA particles as microtemplates by coprecipitating a CaCl2 solution that contains dissolved BSA, with an equimolar Na2 CO3 solution. The microcapsules shell is assembled through a layer-by-layer deposition technique of calcium cross-linked k-carrageenan hydrogel alternating with polyelectrolite complex hydrogel formed via electrostatic interactions between k-carrageenan and chitosan. After the removal of CaCO3 through Ca 2+ complexation with EDTA, and by a slightly treatment with HCl diluted solution, the BSA core is turned into a BSA gel through a thermal treatment. The BSA gel microcapsules were then loaded with curcumin, through a diffusion process from curcumin ethanolic solution. All the synthesized particles and microcapsules were stucturally characterized by: Fourier Transform Infrared Spectroscopy, UV–Vis Spectrometry, X-ray diffraction, thermal analysis, fluorescence spectroscopy, fluorescence optical microscopy, confocal laser scanning microscopy and scanning electron microscopy. The behavior of curcumin loaded microcapsules in media of different pH (SGF, SIF and PBS) was studied in order to reveal the kinetics and the release profile of curcumin. The in vitro evaluation of the antitumoral activity of encapsulated curcumin microcapsules on HeLa cell line and the primary culture of mesenchymal stem cells is the main reason of the microcapsules synthesis as BSA-based vehicle meant to enhance the biodisponibility of curcumin, whose anti-tumor, anti-oxidant and anti-inflammatory properties are well known.